The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"–Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres